Hubungan Pengetahuan Ibu Tentang Pedoman Gizi Seimbang Dan Sosial Ekonomi Dengan Perilaku Kadarzi Di Desa Senggrong Kecamatan Andong Kabupaten Boyolali - SARI, SRI ANIS FADHILA (2016)
Background : Family awarness of nutrition (Kadarzi) can be used a be tool to overcome the nutritions problems because the family has a value strategy as a basis for the development of the society. In a family, mother is the regulator of the family meal. Knowledge will create attitude that will motivate behavior. Family income level is a factor that determines the quality and quantity of the family meal. The level of education also affect family consumption. A higher mother's education, will improve the consumption habits. Purpose : To determine the correlations between mother's knowledge of balanced nutrition guidelines, economic and educational level behavior of Kadarzi. Method : The research type was observational study by using cross sectional design. The respondents were 66 mothers of children under five years old. Method of sampling is was simple random sampling and data analyzed using chi-square. Result : 66,7 % mother's knowledge of balanced nutrition guidelines was good and 33.3% was less. Income levels 80% below the minimum wage. 68.3% mother had the basic of education level, and 75% did not have a behaviour of Kadarzi. Statistical test results obtained a there were no correlation a between mother's knowledge of nutrition guidelines and the behaviour of Kadarzi behavior ;0.725 (p <0.05). There was a relationship between mother's of income with Kadarzi behavior ;0.00 (p <0.05). There is no correlation between mother's education and level of Kadarzi behavior ;0.78 (p <0.05). Conclusion : There was No correlation between mother knowledge about nutritional guidelines and behavior of Kadarzi. There was a correlation betwee income level and behaviour of Kadarzi. There was no correlation between educational level and behaviour of Kadarzi.